The Tendency of Student Motives in Committing Academic Fraud - Melia Bakti Milenia Mintara; Aprina Nugrahesthy Sulistya Hapsari (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
This study aims to examine the effect of fraud diamond’s elements that against the intention of committing academic fraud by comparing two universities in Salatiga. This study used undergraduate accounting students of UKSW and STIE AMA as the object. This study is a quantitative research and data were obtained through distributing questionnaires to respondents via google form. This study used sampling techniques of probability sampling, and total sample of 266 undergraduate accounting students was obtained. The results shows that the variables of pressure, opportunity, rationalization, and capability have a positive effect on the intention of committing academic fraud among UKSW undergraduate accounting students. However, for STIE AMA undergraduate accounting students only pressure and opportunity variables that have a positive effect, while rationalization and capability variables have a negative effect on the intention of committing academic fraud.